2009
DOI: 10.1158/1541-7786.mcr-08-0297
|View full text |Cite
|
Sign up to set email alerts
|

Galectin-1-Mediated Tumor Invasion and Metastasis, Up-Regulated Matrix Metalloproteinase Expression, and Reorganized Actin Cytoskeletons

Abstract: Galectin-1 (Gal-1) is a B-galactose-binding lectin; its expression level has been reported to correlate with tumor progression. Gal-1 is highly expressed in the invasive front of primary tumors and in the cancer cells of metastatic lesions in the lymph nodes of patients with oral squamous cell carcinoma. However, the molecular mechanism of Gal-1 in tumor metastasis is not completely clear. We found that increased Gal-1 expression is closely associated with its high levels of invasion in lung adenocarcinoma and… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
110
1
8

Year Published

2009
2009
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 135 publications
(123 citation statements)
references
References 50 publications
4
110
1
8
Order By: Relevance
“…Indeed, other proteins in the 8505C cell proteomics are described as associated with the tumour growth and metastatic progression: i.e. the S100A6 [42] and LEG1, which, among several functions, is also considered a co-promoter of MMP-2 and MMP-9 expression [43] and therefore an enhancer of tumour invasion and metastasis. In support of this hypothesis is the observation that the 8505C cells produce and release into the medium a significant quantity of matrix metalloproteinases MMP-2 and MMP-9.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, other proteins in the 8505C cell proteomics are described as associated with the tumour growth and metastatic progression: i.e. the S100A6 [42] and LEG1, which, among several functions, is also considered a co-promoter of MMP-2 and MMP-9 expression [43] and therefore an enhancer of tumour invasion and metastasis. In support of this hypothesis is the observation that the 8505C cells produce and release into the medium a significant quantity of matrix metalloproteinases MMP-2 and MMP-9.…”
Section: Discussionmentioning
confidence: 99%
“…The role of Gal-1 in molecular mechanisms leading to cancer development has been analyzed in several tumors (11) but surprisingly never in the molecular pathogenesis of HCC. In particular, it is still unknown whether Gal-1 affects the invasive ability of HCC as previously shown in other malignant tumors (25)(26)(27).…”
Section: Introductionmentioning
confidence: 98%
“…Gal-1 is a multifunctional protein involved in various aspects of tumorigenesis (cell-extracellular matrix and cell-cell interactions, cell migration, angiogenesis, tumor-immune escape) and has been described as a promising cancer target (11)(12)(13). Gal-1 expression has been examined in several malignant tumors (14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24), and its correlation with tumor invasiveness and lymph node metastasis was demonstrated in breast cancer (25), neuroblastoma (26), oral squamous cell carcinoma and lung adenocarcinoma (27). Although Kondoh et al (28) showed that the activation of LGALS1 gene expression in HCC results from promoter hypomethylation, data on Gal-1 protein expression in HCC and its correlation to clinicopathological parameters were not available.…”
Section: Introductionmentioning
confidence: 99%
“…Galectin-1, the first discovered protein in the family, has been found to be upregulated in many cancers, including astrocytoma, melanoma, oral, colon, bladder, and ovarian carcinomas (10)(11)(12). Overexpression of galectin-1 in tumors has also been shown to correlate with the aggressiveness of these tumors and the development of metastasis (11)(12)(13). Moreover, recent studies have also suggested that tumors secrete galectin-1, which contributes to the immunosuppressive response and apoptosis of immune cells, particularly T cells (14)(15)(16).…”
mentioning
confidence: 99%